A Study to Assess the Effectiveness of Self-Instructional Module Regarding Common Psychological Problems of Postpartum Psychosis and Its Management Among Trained Staff Nurses of Netaji Subhash Chandra Bose Medical College, Jabalpur - Anjana Samuel (International Journal of Women's Health Nursing And Practices, 2026)
A quasi-experimental study employing a one-group pretest and posttest design was undertaken to evaluate the impact of a self-instructional module on staff nurses’ knowledge of postpartum psychosis and its management. The research was conducted at Netaji Subhash Chandra Bose Medical College Hospital and included 60 trained staff nurses selected through a non-probability convenience sampling technique. Data were collected through a structured questionnaire designed to assess knowledge levels. The reliability of the instrument was established using the test–retest technique, yielding a reliability coefficient of 0.86, indicating strong consistency. A preliminary pilot study with 10 participants was conducted to evaluate the feasibility and clarity of the tool. Data analysis incorporated both descriptive and inferential statistics, specifically the paired t-test and chi-square test. The findings revealed a marked increase in knowledge following the implementation of the self-instructional module. The average pretest score of 16.03 rose to 31.2 in the posttest, and this improvement was statistically significant at the 0.05 level, demonstrating the effectiveness of the intervention. Additionally, variables such as age, gender, marital status, and years of professional experience showed a significant relationship with baseline knowledge scores. The study concluded that trained staff nurses initially had inadequate knowledge regarding postpartum psychosis, and the self-instructional module was effective in enhancing their knowledge related to early identification and management of the condition.
Keywords: Postpartum psychosis; Self-instructional module; nursing management; psychological problems; staff nurses